2020
DOI: 10.15384/kjhp.2020.20.3.125
|View full text |Cite
|
Sign up to set email alerts
|

N-3 and N-6 Fatty Acid Intakes and Depressive Symptoms in Korean Female Adults Population Using Data from the 2014-2018 Korea National Health and Nutrition Examination Survey

Abstract: Background: This study sought to investigate the association between n-3 and n-6 fatty acid intakes and depressive symptoms in Korean female adults.Methods: Subjects comprised 8,204 Korean female adults, aged over 19 years, who participated in the National Health and Nutrition Examination Survey from 2014-2018. Subjects were classified according to their Patient Health Questionnaire-9 scores into a low depressive symptoms (LDS) group and a high depressive symptoms (HDS) group. Nutrient intake was evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In this study, women who exercised 2–4 and ≥5 times a week were less and more likely to report depressive symptoms when compared with those who exercised 0–1 times a week, respectively. Previous studies 18 19 have reported that low physical activity is associated with depressive symptoms, the results of this study could accurately confirm this due to the limitations of secondary data. In the future, it will be necessary to investigate the effect of exercise on depressive symptoms through repeated studies considering the type of exercise and exercise time.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In this study, women who exercised 2–4 and ≥5 times a week were less and more likely to report depressive symptoms when compared with those who exercised 0–1 times a week, respectively. Previous studies 18 19 have reported that low physical activity is associated with depressive symptoms, the results of this study could accurately confirm this due to the limitations of secondary data. In the future, it will be necessary to investigate the effect of exercise on depressive symptoms through repeated studies considering the type of exercise and exercise time.…”
Section: Discussionsupporting
confidence: 72%
“…Studies on depressive symptoms using the PHQ-9 18 typically define individuals as having depressive symptoms if they score ≥10 points on this survey. However, this study used previous studies 26 27 on pregnancy and childbirth to define depressive symptoms in individuals who scored ≥5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation